How Credit Rating Changes Impact on UK Stock Returns. - TSIANAKAS, KONSTANTINOS / KT (2017)
This research investigates the effects of credit rating changes on equity returns in the UK stock market. This dissertation was conducted using a sample of 152 actual rating changes released by Standard and Poor’s from the period 2000-2017, but not including new ratings and Watch List changes for the same time. After checking and clearing observations that were related with concurrent news, the results of this study show significant abnormal returns for Downgrades, whereas insignificant abnormal returns are found for Upgrades, especially near the announcement day, outputting that way similar results with Choy et al (2006). The findings also suggest that the type of rating change, and the type of industry of the firm, potentially impact on stock prices’ returns. Additionally, little evidence was found for determinants of abnormal returns.